2020
DOI: 10.1080/23802359.2020.1749154
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the deep-water cartilaginous fish Hydrolagus affinis (de Brito Capello, 1868) (Holocephali: Chimaeridae)

Abstract: Cartilaginous fishes are a highly vulnerable vertebrate group but remain poorly studied, especially those occupying deep-water ecological niches. Here, we describe the complete mitogenome of the deep-water chimaeriform Hydrolagus affinis (de Brito Capello, 1868) (Holocephali: Chimaeridae). The mitogenome has 19,437 nucleotides and the same overall content, i.e. 13 protein-coding genes, 22 transfer RNA, 2 ribosomal RNA genes, as available for all cartilaginous fishes mitogenomes. Phylogenetic reconstructions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The paraphyletic status of Hydrolagus and Chimaera was also recovered, as recently reported by Gomes-dos-Santos et al. ( 2020 ). The newly sequenced H. mirabilis mitogenome ranges in the percentage of sequence divergence from 12.8% (unc p -distance) from H. affinis to 15.4% from H. lemures .…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The paraphyletic status of Hydrolagus and Chimaera was also recovered, as recently reported by Gomes-dos-Santos et al. ( 2020 ). The newly sequenced H. mirabilis mitogenome ranges in the percentage of sequence divergence from 12.8% (unc p -distance) from H. affinis to 15.4% from H. lemures .…”
supporting
confidence: 79%
“…Mitogenomes have been a powerful tool used to elucidate phylogenetic relationships, both at deep and at shallow evolutionary nodes (e.g. Inoue et al 2010;Gomes-dos-Santos et al 2020).…”
mentioning
confidence: 99%
“…However, as previously observed (Gomes-dos-Santos et al. 2020 , 2021 ), neither Hydrolagus nor Chimera genera were recovered as monophyletic, which highlights the importance of revising the taxonomy. Indeed, previous authors had already suggested that the distinction between Chimera and Hydrolagus based on the presence or absence of a notch separating the anal from the caudal fin, respectively, needed revision (Didier et al.…”
mentioning
confidence: 52%
“…The recent studies revealed the paraphyletic status of the genus Hydrolagus and Chimera (Gomes-dos-Santos et al. 2020 ; Gomes-dos-Santos et al. 2021 ; Vilas-Arrondo et al.…”
Section: Resultsmentioning
confidence: 99%